Über die Hindernisse der Schnittflächen in zweimaliger Faserung - Matuzevičius, A. (Lithuanian Mathematical Journal, 1961)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:А. Матузявичюс. Препятствия для секущих поверхностей двукратных расслоенийA. Matuzevičius. Kertamųjų paviršių kliūtys dvigubuose sluoksniavimuose